Measuring the concentration of freestream species on a hypersonic transpiration-cooled stagnation point - Ewenz Rocher, M; Hermann, T; McGilvray, M; Grossman, M; Vandeperre, L (American Institute of Aeronautics and Astronautics, 2022)
This paper presents direct surface concentration measurements of a transpiration-cooled stagnation point in hypersonic flow. Pressure-sensitive paint is employed on a porous alumina sample to measure the concentration of freestream species and thus how well the coolant mitigates mass diffusion from the freestream to the surface. Experiments are conducted at Mach 6.9 at three different pitot pressures: 10, 20, and 30 kPa. Porous alumina is chosen due to its ability to bond pressure-sensitive paint and its similar microstructure to porous ultra-high-temperature ceramics. Nitrogen, argon, and krypton are used as injection gases at mass flow rates ranging from 0.01 to 0.55  kg/(m2⋅s), in order to displace up to 99% of the freestream gas at the surface. The experimental data show that transpiration cooling is more effective in displacing freestream gas than predicted by analytical models and numerical solutions. The microheterogeneous surface with recessed pores means that there is an additional pressure gradient within the first layer of pores.